Irrigated rice rotations affect yield and soil organic carbon sequestration in temperate South America. (6th February 2022) - Macedo, Ignacio; Roel, Alvaro; Ayala, Walter; Pravia, M. Virginia; Terra, Jose A.; Pittelkow, Cameron M.
Abstract: Rice ( Oryza sativa L.) systems rotated with perennial pastures have intensified in South America to increase annual grain productivity, but the effects on rice yield and soil quality remain poorly understood. We evaluated rice grain yield, crop and pasture biomass production, and soil organic carbon (SOC) and total nitrogen stocks (0–15‐cm depth) in three rice‐based rotations over 8 yr in Uruguay. Treatments were: (a) rice–pasture [a 5 yr rotation of rice–ryegrass ( Lolium multiflorum Lam.)–rice, then 3.5 yr of a perennial mixture of tall fescue ( Festuca arundinacea Schreb.), white clover ( Trifolium repens L.), and birdsfoot trefoil ( Lotus corniculatus L.)], (b) rice–soybean [a 2‐yr rotation of rice–ryegrass–soybean ( Glycine max [L.] Merr.)–Egyptian clover ( Trifolium alexandrinum L.)], and (c) rice–cover crop (an annual rotation of rice–Egyptian clover). Rice after soybean or pasture achieved the highest yield (9.8 Mg ha –1 ), 9% higher than rice after rice in the rice–pasture and rice–cover crop systems. Estimated belowground biomass under rice–pasture (2.7 Mg ha –1 ) was 12 and 42% greater than under rice–cover crop and rice–soybean rotations, respectively. Rice–pasture showed an increase of 0.6 Mg ha –1  yr –1 of SOC; no changes were observed in the intensified rotations replacing pasture with additional rice or soybean. All systems sustained soil total N. These results provide insights for implementing sustainable rice‐based rotations, with rice–pasture being the only system that increased SOC while achieving high rice yields and belowground biomass productivity. Core Ideas: Rice yield was improved after pasture or soybean but decreased for rice after rice. Intensified stable rice–pasture rotations with rice or soybean did not decrease SOC. The rice–pasture system sequestered 0.6 Mg ha −1  yr −1 SOC during the 8‐yr study. Approximately 1.9 Mg ha −1  yr −1 of belowground biomass was required to sustain SOC.